A Review of the Research on Thermo-Hydro-Mechanical Coupling for the Frozen Soil. (21st March 2022) - Teng, Yun Chao; Teng, Zhen Chao; Liu, Yu; Liu, Xiao Yan; Zhou, Ya Dong; Liu, Jia Lin; Li, Bo
Abstract : This paper reviews the history of the research development on the coupling mechanism of the multiphysical field, e.g., thermo-hydro-mechanical (THM), for frozen soil. The objective is to deepen the current understanding of the theories and mechanism of multiphysical field coupling in the frozen soil and the dynamic changes in the temperature, moisture, and stress fields during soil freezing. A new differential equation of the coupling of temperature field and moisture field is proposed. Based on the DiscreteFrechetDist algorithm, a fitting method of evaluating a curve is proposed. The paper is expected to help understand the soil freezing process in cold regions and enhance the innovativeness of the research methodologies dealing with multifield coupling for the frozen soil.